Challenges of Implementing Corporate Social Responsibility (CSR) and Sustainable Finance in Financing Companies - Pertiwi, Kartika Eka; Dendi Marcello (Universitas Kuningan, 2025)
This study aims to thoroughly analyze the role of Corporate Social Responsibility (CSR) Regulations in Financing Companies and examine the Implementation of CSR Fund Allocation by these ventures. The exploraion also aims to comprehensively investigate the Implementation of CSR and Sustainable Finance at PT BNI Finance in the Context of Sustainable Development Goals (SDGs). In order to achieve the stated objectives, a socio-legal study approach based on previous explorations on various disciplines such as tax, economics, and law was adopted. Accordingly, this investigation utilized primary data obtained through interviews and observations, and secondary data gathered from regulations, journals, and reports. The obtained results showed that CSR was an obligation regulated in the Law on Limited Liability Companies and Financial Services Authority Regulation (FSAR/POJK) on the Implementation of Sustainable Finance for Financial Services Institutions, Issuers, and Public Companies. This obligation applies to PT BNI Finance due to the indirect environmental impact of the main business activity, namely vehicle financing. However, a significant discrepancy was found between the planned CSR fund allocation of IDR 65 million in the Sustainable Finance Action Plan and the actual realization of IDR 28.4 million in 2023. Based on the observations made, approximately 66.7% of the implemented programs were philanthropic and not optimally integrated with sustainable finance principles or SDGs. In essence, an inference was made that the implementation of CSR at PT BNI Finance was not optimal, particularly due to the general nature of existing regulations and the absence of specific technical guidelines.